Penelitian sifat sifat fisika sol plastik - Susilowati Susilowati (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1986)
The physical properties of plastic soles especially flexible soles and spons soles for footwear (shoes, sandals, etc) are very important. This physical properties are : tensile strength; elongation at break; tensile stress at 100%; hardness; density; tear resistance; permanen set; abrasion resistance and flexing. The type of plastic material used for flexible and spons plastic soles, as recorded by infrared spectrophotometry analysis indicate that most of them are made by PVC. Physical test result shown that plastics soles can be graded into three categories in comparation with the specification of the IIS (Indonesian Industial Standard) number SII 1103 – 84.